Distúrbios psíquicos menores em estudantes universitários da área da saúde - Pedro, Cecília Mariane Pinheiro (2017)
Minor psychiatric disorders indicate psychic suffering. In the health field these symptoms can be present since college since this period is permeated by stressing factors. At the beginning of the health care activities, the student is faced with knowledge limitations, as well as, the fear of the unknown and the first contact with illness and death situations. Thereby, it was aimed to identify the factors associated with minor psychiatric disorders and to estimate their prevalence in health college students. It`s a cross-sectional study developed with 792 students enrolled in seven courses in an university in Rio Grande do Sul: Nursing, Pharmacy, Physical Therapy, Speech Therapy, Medicine, Dentistry and Occupational Therapy. The data collection occurred between April and July, 2017, after the approval of the institution Research Ethics Committee and the authorization of the university administration unity. A questionnaire surveying about social demographic, academic and health habits was used along with the Brazilian version of the Self Reporting Questionnaire – 20 for the minor psychiatric disorders evaluation. For the data analysis it was used descriptive statistics through frequency distribution and the measurement of the position and dispersion; and also analytical statistics was used with the chi-square test and the Poisson`s regression, considering as significant the associations with p>0,5. The majority of the participants were female (74,6%), with ages raging from 18 to 20 (42,4%) and their academic enrollment varied between third and sixth semester, being most students with a Medicine major (24,2%). The prevalence of minor psychiatric disorders was 55,4% and the symptoms nervousness/tension/preoccupation were checked with more frequency (84,5%). Moreover, the course with the biggest prevalence was Speech Therapy (85,7%). It was identified as associated factors: being a female, studying Nursing, Pharmacy, Physical Therapy, Speech Therapy or Occupational Therapy, not practicing or practicing occasionally physical activities, being a smoker or consuming tobacco every so often, not having leisure time at all or only sometimes and having a medically diagnosed illness. It was perceived that the mental health of these students needs urgent care, be it by the offer of psychiatric health assistance or through activities that promote mental health. It`s important to highlight that the study`s findings compose important material for the creation of strategies to prevent psychiatric illness during college, while it also contributes to the development of new researches with this subject.